Community Structure of Gastropods in Mangrove Ecosystem in Tanjung Pasir Village, Teluknaga, Tangerang District: - Sasongko, Agung Setyo; Rahmawati, Lutviah (Masyarakat Moluska Indonesia, 2025)
The waters of the dune mangrove harbor a diversity of gastropods that play a vital ecological role. Gastropods are often used as a water bioindicator because of their ability to continue to respond to changes in the water. This study has the purpose of identifying types and analyzing the mollusk community (gastropods) and analyzing the relationship-chemical parameters of the mollusk community. As for the research method used is purposive sampling, the sample take takes place at two stages, namely the gastropod parameters and gastropod samples being taken. The results of the three observation stations in the mangrove cape of the sand yielded 5 species of gastropods and 4 genus. Gastropods spread patterns tend to be uniform and some clustered. The dietal index (h ') of variety (1.03), in turn, the equilibrium (e) group of gastropods tends to be balanced by value (0.64) and then on a non-commissioned (c) index (0.95). Water quality parameters indicate good water conditions. Thus, the entire structure of gastropods communities in the mangrove waters tended to be stable.